Potential Keratinase-Producing Bacteria Isolated from Pangasius (Pangasianodon hypophthalmus) Farms Fed with Poultry Waste: Keratinase-Producing Bacteria from Pangasius Culture Farms - Greeshma, S. S.; Mathew, Merlin; Murugadas, V.; Pillai, Devika (Fishery Technology, 2025)
Keratinase-producing bacteria degrade keratin, a tough protein found in feathers, hair, nails, and other keratinized materials. Mud, water, and fish samples from ten poultry waste-fed, Pangasianodon hypophthalmus farms in Palakkad and Alappuzha districts of Kerala, India, were screened for keratinolytic bacteria. Among 116 proteolytic isolates, 6.9% showed keratinolytic activity on feather meal agar. Three isolates namely FWKB1, FMKB1 and FMKB2 were identified as having good keratinolytic potential. FMKB1 and FMKB2 isolated from soil samples in Palakkad were identified as Bacillus subtilis, while FWKB1 isolated from a water sample in Alappuzha was identified as Exiguobacterium profundum. In vitro enzyme assays revealed that FMKB1 and FMKB2 produced 53.2 U/mL and 66.8 U/mL of keratinase enzyme, respectively within 24h of incubation at 37°C. A direct keratinase assay with raw feathers exhibited 72.8 U/mL enzyme production by a combination of FMKB1 and FMKB2, completely degrading raw feathers within 45 days at 37°C. Characterisation of exo-enzyme production revealed the absence of lipase, gelatinase, and amylase enzymes. Haemolysis, Congo red binding, biofilm formation and the production of AHL signalling molecule were not detected in the bacterial isolates tested. These isolates can be promoted as environmental probiotics in aquaculture farms for waste management and protein recycling.